MENINGKATKAN KETERAMPILAN BOLA BASKET DENGAN METODE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA FILM - Muhadi, Muhadi (JURNAL SINEKTIK, 2023)
The purpose of this study is to describe Basketball learning with the Teams Games Tournament (TGT) Method assisted by film media and analyze the Basketball skills of Class VI students of SD Negeri 3 Waru with the Teams Games Tournament (TGT) Method assisted by film media. This type of research is Classroom Action Research (PTK). The action in the study is the Teams Games Tournament (TGT) Method assisted by film media. The research was conducted in Class VI of SD Negeri 3 Waru. The research took place at the beginning of Semeter I of the 2018/2019 Academic Year. The subjects of the study were thirty-five learners, consisting of twenty sons and fifteen daughters. Data collection techniques are non-test techniques and test techniques. Data collection tools are observation sheets, stop watches and documentation. Data analysis techniques are comparative descriptive. The result of the study was that the Basketball skills of Class VI students of SD Negeri 3 Waru with the Teams Games Tournament (TGT) Method assisted by film media increased, so it was included in the satisfactory category.